Integrasi Nilai-Nilai Multikultural Dalam Kurikulum Pendidikan Islam Madrasah Tsanawiyah: Perspektif Politik Pendidikan - Yesi Arikarani; Hecksa Manora; Nurlila Kamsi; Imam Mahdi; Adisel (Edification Journal : Pendidikan Agama Islam, 2026)
Islamic education in Madrasah Tsanawiyah plays a strategic role in fostering a tolerant, inclusive, and moderate generation within a pluralistic society. The integration of multicultural values into the Islamic Religious Education (PAI) curriculum is essential for strengthening social cohesion, promoting mutual respect, and preventing intolerance. This study aims to analyze the influence of educational political policies on the implementation of multicultural values in the PAI curriculum and to identify the associated challenges and opportunities. The research employs a qualitative library research approach through the analysis of scholarly literature, educational regulations, and relevant policy documents. That policies such as the Independent Curriculum, the Pancasila Student Profile, and the Rahmatan lil ‘Alamin Student Profile provide a formal foundation for integrating multicultural values into curriculum content, learning processes, and school culture. However, limited teacher competence, insufficient contextual teaching materials, monocultural perspectives, and identity politicization remain significant challenges that require collaborative and sustainable solutions.